INTERCASTE MARRIAGE IN THE CONTEXT OF TORAJA: Towards Contextual Theology Of Intercaste Marriage In Toraja - Taruk, Elim Wilsen (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2021)
Intercaste marriage is also one of the crucial problems face by an ethnic group called Toraja, an ethnic group which belongs to the province of South Sulawesi in Indonesia. Although according to the Declaration of Human Rights Article 16.1/2 that marriage is an independent decision, but it should wait when comes to the lives of the Toraja. Although it is also specifically explained according to the 1974 Marriage Law in Indonesia that the validity of marriage can only be legally recognized when performed according to the religion of both couples, so that religion can be considered as the main issue for the Indonesian when comes to the issue of marriage, but it is clear that it is not the case for the Toraja. The main issue lies on caste, as the Toraja also consists of four castes which derived from the indigenous belief, Aluk Todolo, which is believed as something transcendental-ontological, therefore inviolable even through marriages. However, as Christianity has become the most dominant religion embraced by the Toraja, therefore it is worthy to ask the roles of Christian teachings in their lives. the question posed: “What is a liberative theological approach to the intercaste marriage in Toraja?” The voices from the margins, of the intercaste couples, have revealed how they have been struggling with the discriminatory acts they have received even from their fellow Church members (pastors, elders in society and lay people of the church). They have started to ask the roles of Christ’s love which has set His people free from all kind of jail in this world, and that Christ Himself has demonstrated that all people are equal before Him. This article aims to show the lived experiences of the intercaste couples in Toraja, and how their voices could become the starting point for the Toraja Church to construct a liberative contextual theology of intercaste marriage, assisted by the approaches of feminist liberation theology (which always focuses on the lived experiences) and postcolonial criticism which has helped to identify the Toraja subaltern. Furthermore, the results are also helpful to contribute some concrete recommendations for the Toraja Church to be taken against their intercaste couples and commit to stand to advocate them, and especially to do some pastoral care to recover their condition both mentally and spiritually.